Corporate Reputation Measurement: Alternative Factor Structures, Nomological Validity, and Organizational Outcomes - Agarwal, James; Osiyevskyy, Oleksiy; Feldman, Percy M.; Marquina, Percy Samoel (Journal of business ethics, 2015)
Management scholars have paid close attention to the construct of organizational or corporate reputation (CR), particularly in the applied business ethics and corporate social responsibility (CSR) fields. Extant research demonstrates that CR is one of the key mediators between CSR and important organizational outcomes, which ultimately improve organizational performance. Yet, hitherto the research focused on CR construct has been plagued by multiple definitions, conflicting conceptualizations, and unclear operationalizations. The purpose of this article is to provide theoretical ground for positioning of CR as an assessment construct that is modeled as a second-order factor affecting individual first-order dimensions (having a reflective nature), and to provide methodological and empirical support toward such conceptualization. We assert that intangible, socially complex, and causally ambiguous CR (latent construct) can be accurately estimated through its individual measurable dimensions. Using survey data from Peru, we empirically test the hypothesized second-order reflective model within a hierarchy of nested and non-nested models, and compare its model fit and predictive power (nomological validity) with alternative conceptualizations. Modeling CR as a second-order reflective construct relies on a set of theoretical propositions and yields several methodological advantages, including strong conceptual interpretability and parsimony when tested within a nomological context. We explicitly demonstrate positive organizational outcomes of CR: customer trust, corporate identification, in-role behavior, and extra-role behavior. Then, we demonstrate that the shorter scales of CR can be used as a good proxy for the full construct measure. The paper concludes by highlighting theoretical insights, and methodological and managerial implications of the findings.